Regulating the non-consensual sharing of intimate images ('revenge pornography') via a civil penalty regime: a sex equality Perspective - Evans, Michelle (Monash University, 2019)
The ‘non-consensual sharing of intimate images’, more commonly known as ‘revenge pornography’, is a widespread issue, which can have devastating consequences for victims. However, it is an area where the law has only just started responding to technology, with legislative reforms in several states including South Australia, Victoria, New South Wales, the Australian Capital Territory and Western Australia. This paper provides an overview of relevant state and federal laws. Its main focus is to critique the most recent Commonwealth legislative reforms to regulate the nonconsensual sharing of intimate images via a civil penalties regime. These reforms were made by the Enhancing Online Safety (Non-Consensual Sharing of Intimate Images) Act 2018 (Cth), which amended the Enhancing Online Safety Act 2015 (Cth). This paper critiques the civil penalties regime from a sex equality perspective, and makes suggestions to improve the reforms so that victims are better protected and empowered.